2023
DOI: 10.1002/ski2.265
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative analysis of individual experiences post botulinum toxin injection ‐ United Kingdom Survey

Abstract: IntroductionIn the United Kingdom (UK), complications that arise following the administration of Botulinum Toxin are reported to the Medicines and Health Regulatory Agency (MHRA) via the Yellow Card Reporting Scheme. Over the past decade, there has been a significant increase in the number of non‐surgical aesthetic procedures. Concerns have been raised that the MHRA is not fully capturing complications in terms of volume and impact on patients.AimThis novel study explores the lived experiences of individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A recent mixed-methods study surveying adverse effects experienced by over 500 patients has demonstrated the significant impact of such effects on emotional well-being. 4 This report also highlighted, concerningly, that 84% of respondents did not know who regulates the aesthetic industry with 78.4% of patients feeling that their practitioner refused to support them when they reported adverse effects. These findings are at odds with earlier studies performed more than 15 years ago, which reported high levels of satisfaction with botulinum toxin injections.…”
Section: Self-perception Of Natural Outcome Appearance and Emotional ...mentioning
confidence: 93%
See 1 more Smart Citation
“…A recent mixed-methods study surveying adverse effects experienced by over 500 patients has demonstrated the significant impact of such effects on emotional well-being. 4 This report also highlighted, concerningly, that 84% of respondents did not know who regulates the aesthetic industry with 78.4% of patients feeling that their practitioner refused to support them when they reported adverse effects. These findings are at odds with earlier studies performed more than 15 years ago, which reported high levels of satisfaction with botulinum toxin injections.…”
Section: Self-perception Of Natural Outcome Appearance and Emotional ...mentioning
confidence: 93%
“…Furthermore, there are concerns that reporting mechanisms for complications in the UK are inadequate or inaccessible, which may lead to under-representation of adverse events. 4 A significantly greater number of practitioners who are not doctors are now delivering botulinum toxin as a cosmetic injectable therapy and not enough is known about how this affects patient safety and outcomes.…”
Section: Self-perception Of Natural Outcome Appearance and Emotional ...mentioning
confidence: 99%